An etching method for improving the resistance of fused quartz components to ultraviolet laser-induced damage
By adding oxygen to dry etching technology or using oxygen plasma for post-treatment, the problems of insufficient improvement in laser damage resistance and safety and environmental protection of fused quartz components in the prior art are solved, and the effect of significantly improving the damage resistance of the component is achieved.
Patent Information
- Application Number
- CN202310480173.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-04-28
AI Technical Summary
When the prior art improves the resistance of ultraviolet laser-induced damage to fused quartz components, there are problems such as isotropic etching characteristics that cannot completely remove topological structures such as scratches and pits, resulting in increased surface roughness of the component and decreased optical performance indicators. At the same time, the use of hydrofluoric acid has problems such as safety risks and heavy environmental protection burden.
The pure dry etching technology is used to perform surface post-treatment of fused quartz components. By adding oxygen to the raw material gas or post-treatment with oxygen plasma after etching is completed, the generation of secondary defects is suppressed or repaired, and the component's damage resistance is improved.
The zero-probability damage threshold of fused quartz components is significantly improved, which can be increased by nearly 1 times compared with the original polished samples, solving the problem of insufficient improvement in damage performance of secondary defects in dry etching technology, and at the same time avoiding the use of hydrofluoric acid, reducing safety risks and environmental protection burden.
Smart Images

Figure CN116444167B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fused quartz component processing, and in particular relates to an etching method for improving the anti-ultraviolet laser induced damage performance of a fused quartz component. Background Art
[0002] The problem of ultraviolet laser-induced damage on the surface of fused quartz components is a bottleneck that limits the improvement of the load capacity of high-power laser systems. The root cause of the damage lies in the various defects introduced on the component surface during the previous processing processes such as polishing and grinding. Therefore, removing these defects through surface post-processing technology of components is the key to improving the performance of fused quartz components in resisting laser-induced damage. At present, the surface post-processing technologies for defect removal and damage resistance improvement of fused quartz components mainly include wet etching, dry etching and composite etching technology combining dry and wet etching.
[0003] The representative of wet etching technology is dynamic chemical etching technology (DCE) based on HF / NH4F slow-release solution. Its basic idea is to use the reaction between hydrofluoric acid and SiO2 to dissolve the polishing and re-deposition layer on the surface of the component under a certain temperature rise and the assistance of ultrasonic oscillation, so that the scratches and cracks in the sub-surface defect layer are exposed and gradually widened and enlarged, passivating electronic defects, and at the same time slowly releasing impurity defects such as polishing powder embedded therein, thereby improving the damage resistance of the component. Dynamic chemical etching technology has a very significant effect on improving the damage resistance of fused quartz components. Under deep etching (20μm), the zero-probability damage threshold of the component surface can be increased by nearly 1 times compared with the original polished sample. However, the isotropic etching characteristics of this method determine that it cannot completely remove topological structures such as scratches and pits in the sub-surface layer of fused quartz, but continuously replicates and amplifies them, which ultimately leads to an increase in the surface roughness of the component and a decrease in optical performance indicators. In addition, hydrofluoric acid, as a highly dangerous chemical, poses an extremely high safety risk to the entire post-processing process, while the reduced utilization rate of the etchant caused by the precipitation of etching products adds a great burden to acid treatment and environmental protection.
[0004] The representative of dry etching technology is reactive ion etching (RIE) technology based on fluorocarbon plasma. Its basic idea is to use fluorocarbon gas (CF4 or CHF3, etc.) and active particles in Ar mixed plasma to physically bombard the fused quartz surface and react with gas phase chemical reaction to achieve etching and removal of the surface material of the component, and the defects embedded in it are removed. Reactive ion etching technology has the characteristics of anisotropic etching. It can achieve traceless stripping of sub-surface defects of components under shallow etching. It can perfectly avoid the problems of decreased optical performance indicators and poor safety of components in dynamic chemical etching technology. It is a very attractive defect removal method. However, the current reactive ion etching technology has a fatal weakness of insufficient improvement in component damage resistance. Compared with the original polished component, its zero probability damage threshold is improved by less than 50%. The root cause is that the secondary defects in the etching process limit the improvement of damage performance.
[0005] Composite etching technology combines dry etching and wet etching. First, RIE is used to remove the original surface and sub-surface defects of the component, and then DCE is used to remove the secondary defects of RIE. RIE+DCE composite etching technology can better solve the problem of secondary defects of RIE, and achieves a significant improvement in component damage resistance while maintaining the original polished surface quality. However, this method reintroduces the use of hydrofluoric acid. Although the amount of hydrofluoric acid is reduced compared to pure DCE technology, it still cannot escape the problems faced by hydrofluoric acid etching, such as redeposition of reaction products, poor safety, and heavy environmental burden. More importantly, the combination of dry and wet etching to process fused quartz components of various sizes will inevitably lead to cumbersome process flows and seriously reduce the post-processing efficiency of components. Summary of the invention
[0006] In view of the various deficiencies of the prior art and in order to solve the above problems, an etching method for improving the resistance of fused quartz components to ultraviolet laser induced damage is proposed.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] An etching method for improving the ultraviolet laser induced damage resistance of a fused quartz component, comprising:
[0009] The surface of the fused quartz component is subjected to reactive ion etching treatment, wherein the plasma used in the reactive ion etching includes fluorocarbon plasma, argon plasma and oxygen plasma.
[0010] The technical solution is further configured to place the fused quartz component in a plasma chamber of a reactive ion etcher, evacuate the plasma chamber, introduce raw gas, and turn on a plasma radio frequency power supply to generate plasma to etch the fused quartz component.
[0011] The technical solution is further configured to include, before the surface of the fused quartz element is subjected to reactive ion etching, the following steps are further included:
[0012] A confocal fluorescence microscope is used to evaluate the subsurface defect depth of the fused quartz component, the etching rate of the reactive ion etcher is calibrated, and the reactive ion etching processing time is determined according to the etching depth and the etching rate. The etching depth is not less than the subsurface defect depth.
[0013] The technical solution is further configured as follows: placing the fused quartz component in a plasma chamber of a reactive ion etcher, evacuating the plasma chamber, introducing a mixed gas of fluorocarbon gas, argon gas and oxygen, wherein the mixed gas is used as a raw gas, and turning on a plasma radio frequency power supply to generate plasma to etch the fused quartz component.
[0014] The technical solution is further configured as follows: placing the fused quartz component in a plasma chamber of a reactive ion etcher, and after evacuating the plasma chamber, introducing a mixed gas of fluorocarbon gas and argon gas, wherein the mixed gas is used as a raw material gas, and turning on a plasma radio frequency power supply to generate plasma to etch the fused quartz component. After etching is completed, the raw material gas is switched to oxygen, and the fused quartz component is continued to be processed with oxygen plasma.
[0015] The technical solution is further configured to include alkaline cleaning and ultrapure water cleaning of the fused quartz element before the reactive ion etching treatment of the surface of the fused quartz element, and drying the fused quartz element after the cleaning is completed, wherein the alkaline cleaning and the ultrapure water cleaning are performed in an ultrasonic cleaning machine.
[0016] The technical solution is further configured to include, after the surface of the fused quartz element is subjected to reactive ion etching treatment, alkali cleaning and ultrapure water cleaning of the treated fused quartz element are also included, and the alkali cleaning and ultrapure water cleaning are performed in an ultrasonic cleaning machine after the cleaning is completed.
[0017] The technical solution is further configured that the cleaning agent used in the alkaline cleaning is Micro-90 solution, and the alkaline cleaning and the ultrapure water cleaning are carried out in a Class 100 clean environment.
[0018] The beneficial effects of the present invention are:
[0019] 1. Pure dry etching is used to post-treat the surface of fused quartz components. Based on the existing reactive ion etching technology, a certain amount of oxygen is added to the raw gas, or the sample is treated with oxygen plasma for a certain period of time after etching is completed, so as to inhibit or repair the generation of secondary defects and improve the damage resistance of the components.
[0020] 2. The advantages of dry etching technology are retained, and at the same time, the problem of insufficient improvement in damage performance caused by its secondary defects is solved without increasing any technical complexity.
[0021] 3. The zero-probability damage threshold of the fused quartz element processed by the present invention can be increased by nearly 1 times compared with the original polished sample, and can be increased by more than 50% compared with the existing dry etching technology, and the damage performance improvement effect is significant.
[0022] 4. Compared with dynamic chemical etching technology and RIE+DCE composite etching technology, the present invention adopts pure dry etching technology, which completely avoids the use of hydrofluoric acid, greatly reduces safety risks and environmental burdens, simplifies the processing flow, and is more in line with the development principles of safety, greenness and efficiency.
[0023] 5. The operation steps are simple, the operating conditions are mild, the repeatability is strong, it is suitable for continuous mass production, and the environmental pollution is small. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a flow chart of an etching method for improving the resistance of fused quartz components to ultraviolet laser induced damage according to an exemplary embodiment;
[0025] Figure 2 is a schematic diagram comparing the surface damage performance of samples in Example 2;
[0026] Figure 3 is a schematic diagram comparing the surface damage performance of the samples in Example 3;
[0027] Figure 4 is a schematic diagram comparing the surface damage performance of samples in Example 4;
[0028] Figure 5 It is a schematic diagram comparing the surface damage performance of the samples in Example 5. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments in this application, other similar embodiments obtained by ordinary technicians in this field without making creative work should all fall within the scope of protection of this application. In addition, the directional words mentioned in the following embodiments, such as "up", "down", "left", "right", etc., are only reference to the directions of the accompanying drawings. Therefore, the directional words used are used to illustrate rather than limit the invention.
[0030] Embodiment 1:
[0031] Figure 1The present invention is a flow chart of an etching method for improving the ultraviolet laser induced damage resistance of a fused quartz component according to an exemplary embodiment, the method comprising:
[0032] S100, cleaning the fused quartz element with alkali and ultrapure water, and drying it after cleaning.
[0033] It is worth noting that fused quartz material is a component that must be used in laser driving devices, and the amount used is very large. For fused quartz components with certain functional characteristics, they may lose their original good functions due to surface roughness and surface deterioration. In addition, if the surface of the fused quartz component is too rough, it will also affect its damage resistance. It can be seen that it is particularly important to control the roughness of the surface of the fused quartz component. The alkaline cleaning and the ultrapure water cleaning are carried out in an ultrasonic cleaning machine, which is conducive to the clean treatment of the surface of the fused quartz component and enhances the cleaning effect.
[0034] S200, performing reactive ion etching on the surface of the fused quartz component, wherein the plasma used in the reactive ion etching includes fluorocarbon plasma, argon plasma and oxygen plasma.
[0035] Specifically, the fused quartz component is placed in a plasma chamber of a reactive ion etcher, the plasma chamber is evacuated, raw material gas is introduced, and a plasma radio frequency power supply is turned on to generate plasma to etch the fused quartz component.
[0036] Among them, the raw gas includes fluorocarbon gas, argon gas and oxygen. The fluorocarbon gas is CF4 or CHF3. The main component of the fused quartz element is SiO2. Generally, CF4 or CHF3 is used to etch SiO2. However, CHF3 is easier to control the deposition of fluorocarbon polymers and can ensure a better surface roughness. Argon plasma mainly bombards the surface of the fused quartz element through charged ions, which will smooth the rough edges and corners on the surface and further reduce the surface roughness. Oxygen plasma can inhibit the generation of secondary defects.
[0037] Before the reactive ion etching treatment of the surface of the fused quartz component, the following steps are also included:
[0038] A confocal fluorescence microscope is used to evaluate the subsurface defect depth of the fused quartz component, the etching rate of the reactive ion etcher is calibrated, and the reactive ion etching processing time is determined according to the etching depth and the etching rate. The etching depth is not less than the subsurface defect depth.
[0039] In this embodiment, a fused quartz component is placed in a plasma chamber of a reactive ion etcher. After the plasma chamber is evacuated, a mixed gas of fluorocarbon gas, argon gas and oxygen is introduced, wherein the gas flow ratio of the fluorocarbon gas, argon gas and oxygen is 14:1:1. The mixed gas is used as a raw gas, and a plasma radio frequency power supply is turned on to generate plasma to etch the fused quartz component.
[0040] It is worth noting that adding a certain amount of oxygen to the raw gas can inhibit the combination of F element and fused quartz matrix and inhibit the generation of secondary defects.
[0041] In some other embodiments, the fused quartz component is placed in a plasma chamber of a reactive ion etcher, and after the plasma chamber is evacuated, a mixed gas of fluorocarbon gas and argon gas is introduced, and the mixed gas is used as a raw material gas. The plasma radio frequency power supply is turned on to generate plasma to etch the fused quartz component. After the etching is completed, the raw material gas is switched to oxygen, and the fused quartz component is continued to be processed with oxygen plasma.
[0042] It is worth noting that after etching is completed, the fused quartz component is treated with oxygen plasma for a certain period of time to repair secondary defects generated during the etching process.
[0043] S300, cleaning the treated fused quartz element with alkali and ultrapure water, and drying it after cleaning.
[0044] Likewise, the alkaline cleaning and the ultrapure water cleaning are performed in an ultrasonic cleaning machine, the cleaning agent used in the alkaline cleaning is Micro-90 solution, and the alkaline cleaning and the ultrapure water cleaning are performed in a Class 100 clean environment.
[0045] Embodiment 2:
[0046] The same parts of this embodiment as those of the first embodiment are not described in detail, except that:
[0047] Three 50mm×50mm×5mm polished fused quartz samples were taken, cleaned and dried, and the depth of the subsurface defect layer was confirmed to be below 1μm by confocal fluorescence microscopy. Among them, one sample was not treated in any way; one sample was etched by CHF3 and Ar (the gas flow ratio was 14:1) plasma for 30min (etching depth 1μm); one sample was etched by fluorocarbon plasma under the same conditions and then treated with oxygen plasma with a power of 50W for 5 minutes, and the gas flow ratio of CHF3, Ar and O2 was 14:1:6.
[0048] The damage performance of three samples was tested using the 1-on-1 damage test method. The results are as follows: Figure 2 As shown. Figure 2It can be seen that the damage resistance of the sample etched by fluorine-carbon plasma has been significantly improved compared with the original sample, and the post-treatment with oxygen plasma can further improve the damage resistance of the sample, and the zero probability damage threshold is increased from 11J / cm 2 and 13 J / cm2 using only fluorocarbon plasma etching 2 Increased to 14J / cm 2 .
[0049] Embodiment three:
[0050] The same parts of this embodiment as those of the first embodiment are not described in detail, except that:
[0051] Three 50mm×50mm×5mm polished fused quartz samples were taken, cleaned and dried, and the depth of the subsurface defect layer was confirmed to be below 1μm by confocal fluorescence microscopy. Among them, one sample was not treated in any way; one sample was etched by CHF3 and Ar (the gas flow ratio was 14:1) plasma for 30 minutes; one sample was etched by fluorocarbon plasma under the same conditions and then treated with oxygen plasma with a power of 20W for 5 minutes, and the gas flow ratio of CHF3, Ar and O2 was 14:1:6.
[0052] The damage performance of three samples was tested using the 1-on-1 damage test method. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that compared with the samples etched only with fluorocarbon plasma, the damage resistance of the samples can be significantly improved by post-treatment with oxygen plasma, and the zero probability damage threshold is increased from 13J / cm 2 Increased to 15J / cm 2 .
[0053] Embodiment 4:
[0054] The same parts of this embodiment as those of the first embodiment are not described in detail, except that:
[0055] Three 50mm×50mm×5mm polished fused quartz samples were taken, cleaned and dried, and the depth of the subsurface defect layer was confirmed to be below 1μm by confocal fluorescence microscopy. Among them, one sample was not treated in any way; one sample was etched by CHF3 and Ar (the gas flow ratio was 14:1) plasma for 30 minutes; one sample was etched by fluorine-carbon plasma under the same conditions and then treated with oxygen plasma with a power of 20W for 5 minutes, and the gas flow ratio of CHF3, Ar and O2 was 14:1:2.
[0056] The surface damage performance of three samples was tested using the 1-on-1 damage test method. The results are as follows: Figure 4 As shown. Figure 4It can be seen that compared with the samples treated with fluorocarbon plasma only, the post-treatment with oxygen plasma under this condition can significantly improve the damage resistance, and the zero probability damage threshold is increased from 13J / cm 2 Increased to 17J / cm 2 .
[0057] Embodiment five:
[0058] The same parts of this embodiment as those of the first embodiment are not described in detail, except that:
[0059] Three 50mm×50mm×5mm polished fused quartz samples were taken, cleaned and dried, and the depth of the subsurface defect layer was confirmed to be less than 1μm by confocal fluorescence microscopy. Among them, one sample was not treated in any way; one sample was etched by CHF3 and Ar (the gas flow ratio was 14:1) plasma for 30 minutes; and one sample was etched by CHF3, Ar and O2 (the gas flow ratio was 14:1:1) mixed gas plasma for 30 minutes.
[0060] The surface damage performance of three samples was tested using the 1-on-1 damage test method. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that compared with pure fluorocarbon plasma, adding oxygen to fluorocarbon plasma can greatly improve the damage performance, and the zero probability damage threshold is increased from 13J / cm 2 Increased to 20J / cm 2 At the same time, the results also show that compared with the method of post-treating with oxygen plasma after fluorocarbon plasma etching in Examples 2 to 4, the method of adding O2 to the raw gas during the etching process is simpler and has better effects.
[0061] The present invention has been described in detail above. The above description is only a preferred embodiment of the present invention and should not limit the scope of implementation of the present invention. That is, all equivalent changes and modifications made within the scope of this application should still fall within the scope of the present invention.
Claims
1. An etching method for improving the resistance of fused quartz components to ultraviolet laser induced damage, characterized in that: The fused quartz component is placed in a plasma chamber of a reactive ion etcher, the plasma chamber is evacuated, a raw material gas is introduced, and a plasma radio frequency power supply is turned on to generate plasma to perform reactive ion etching on the fused quartz component, wherein the plasma used in the reactive ion etching includes fluorocarbon plasma, argon plasma and oxygen plasma; The raw gas includes fluorocarbon gas, argon gas and oxygen. The gas flow ratio of the fluorocarbon gas and the argon gas is 14:
1. The fluorocarbon gas is CHF3. A certain amount of oxygen is added to the raw gas to inhibit the combination of the F element and the fused quartz matrix and the generation of secondary defects.
2. The etching method for improving the ultraviolet laser induced damage resistance of fused quartz components according to claim 1, characterized in that: Before the reactive ion etching treatment of the surface of the fused quartz component, the following steps are also included: A confocal fluorescence microscope is used to evaluate the subsurface defect depth of the fused quartz component, the etching rate of the reactive ion etcher is calibrated, and the reactive ion etching processing time is determined according to the etching depth and the etching rate. The etching depth is not less than the subsurface defect depth.
3. The etching method for improving the ultraviolet laser induced damage resistance of fused quartz components according to claim 2, characterized in that: The fused quartz component is placed in the plasma chamber of a reactive ion etcher. After the plasma chamber is evacuated, a mixed gas of fluorocarbon gas, argon gas and oxygen is introduced. The mixed gas is used as a raw material gas. The plasma radio frequency power supply is turned on to generate plasma to etch the fused quartz component.
4. The etching method for improving the ultraviolet laser induced damage resistance of fused quartz components according to claim 2, characterized in that: The fused quartz component is placed in the plasma chamber of the reactive ion etcher. After the plasma chamber is evacuated, a mixed gas of fluorocarbon gas and argon gas is introduced. The mixed gas is used as the raw material gas. The plasma radio frequency power supply is turned on to generate plasma to etch the fused quartz component. After the etching is completed, the raw material gas is switched to oxygen, and the fused quartz component is continued to be processed with oxygen plasma.
5. The etching method for improving the ultraviolet laser induced damage resistance of fused quartz components according to claim 1, characterized in that: Before the reactive ion etching treatment is performed on the surface of the fused quartz element, the fused quartz element is also subjected to alkaline cleaning and ultrapure water cleaning, and then air-dried after the cleaning is completed. The alkaline cleaning and the ultrapure water cleaning are performed in an ultrasonic cleaning machine.
6. The etching method for improving the ultraviolet laser induced damage resistance of fused quartz components according to claim 1, characterized in that: After the surface of the fused quartz element is subjected to reactive ion etching, the treated fused quartz element is further subjected to alkali cleaning and ultrapure water cleaning, and then air-dried. The alkali cleaning and ultrapure water cleaning are performed in an ultrasonic cleaning machine.
7. An etching method for improving the resistance of fused quartz components to ultraviolet laser induced damage according to claim 5 or 6, characterized in that: The cleaning agent used in the alkaline cleaning is Micro-90 solution, and the alkaline cleaning and the ultrapure water cleaning are carried out in a Class 100 clean environment.
Citation Information
Patent Citations
Method for improving damage threshold of fused quartz optical element
CN103449731A